Fulfillment of essential requirements by private health services of first and second level in bogotá d.c. (2001)
Quality of health care services is an issue of growing interest. This study describes the fulfillment of essential requirements (Resolution 4252/1996) by private health services of first and second level in Bogotá D.C. With the registers of surveillance and control commissions (july/1998 to may/2000) a descriptive study was realized. The variables analyzed were: locality, local socioeconomic level, local residential density, health service supplies, and fulfillment of essential requirements. In Bogotá there are 12 587 health care centers of first and second level. 72,1 % is in Chapinero, Usaquén, and Teusaquillo localities. Only 6,9 % of these centers obey the essential requirements. The findings of this study suggest an "epidemiology of quality" of health care services in Bogotá. In this profile, the rich people have good health services and the poor population has a poor quality health services.